Obsessive - compulsive disorder - course during pregnancy, exacerbation factors - literature review - Julia Czarnota; Katarzyna Cichoń; Małgorzata Chyćko; Agata Kromer; Magdalena Alicja Zapała; Agnieszka Gawryś; Agnieszka Środoń; Monika Łapaj; Joanna Wilk; Małgorzata Maria Cholewa (Journal of Education, Health and Sport, 2023)
Introduction and purpose of the work: